2013
DOI: 10.1177/1545968313496322
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Modified Constraint-Induced Movement Therapy With and Without an Intensive Therapy Program in Children With Unilateral Cerebral Palsy

Abstract: The combination of m-CIMT with an intensive therapy program on distal hand function and strength enhances the effects of m-CIMT alone for improving bimanual performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 30 publications
1
57
1
5
Order By: Relevance
“…24 In the present study, a difference in responsiveness was observed between the two age groups (i.e. While it has previously been suggested that older children may encounter reduced changes because of less plasticity of the brain, notably during CIMT, 26,27 opposite findings were proposed by Sakzewski et al, 28 suggesting that best responders were older children. One possible explanation, consistent with the general idea of the 'Kennard Principle', 25 might be that neuroplasticity is lower in adolescents and that less manual ability improvement can be obtained in this group over a 2 to 3 weeks' intervention in comparison to younger children.…”
Section: Discussioncontrasting
confidence: 51%
“…24 In the present study, a difference in responsiveness was observed between the two age groups (i.e. While it has previously been suggested that older children may encounter reduced changes because of less plasticity of the brain, notably during CIMT, 26,27 opposite findings were proposed by Sakzewski et al, 28 suggesting that best responders were older children. One possible explanation, consistent with the general idea of the 'Kennard Principle', 25 might be that neuroplasticity is lower in adolescents and that less manual ability improvement can be obtained in this group over a 2 to 3 weeks' intervention in comparison to younger children.…”
Section: Discussioncontrasting
confidence: 51%
“…"Modified constraint induced movement therapy (mCIMT)" (Hoare, Imms, Villanueva, Rawicki, Matyas, & Carey, 2013;Klingels et al, 2013;Wallen, Ziviani, Naylor, Evans, Novak, & Herbert, 2011 …”
Section: Resultsmentioning
confidence: 99%
“…Home programs were provided in 31 (52%) of studies however only 7 (23%) provided adequate description to replicate the programs or details on how to obtain the program from authors. Home programs were variously described as lists of activities, manual of exercises (Klingels et al, 2013), home program with neurodevelopmental activities (Law, Cadman, Rosenbaum, Walter, Russell, & Dematteo, 1991;Law, Russell, Pollock, Rosenbaum, Walter, & King, 1997) or written lists of training tasks (Taub, Griffin, Uswatte, Gammons, Nick, & Law, 2011). Four studies provided details of the content and structure of the home program (Aarts et al, 2012;Abd El-Kafy et al, 2014;Deppe et al, 2013;Eliasson, Shaw, Berg, & Krumlinde-Sundholm, 2011), three described commercially available video or web-based games (Chiu et al, 2014;James et al, 2015;Zoccolillo et al, 2015) and the remaining studies had inadequate details to replicate either the structure or content of the home program.…”
Section: Research Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 Intensive hand therapy is costly and typically requires a great amount of time and family commitment. constraint-induced movement therapy (CIMT) or intensive bimanual therapy) has been shown to be effective in improving children's hand function at a group level, there is high variability in outcomes among individuals.…”
Section: Potential Impact Of Corticospinal Tract Organization On Chilmentioning
confidence: 99%